Recent Advances in Combinations of TLC With MALDI and Other Desorption/Ionization Mass-Spectrometry Techniques - Borisov, Roman; Kanateva, Anastasiia; Zhilyaev, Dmitry (Frontiers in Chemistry, 2021)
The combination of planar chromatography with desorption/ionization mass spectrometry (MS) techniques provides chemists with unique tools for fast and simple separation of mixtures followed by detection of analytes by the most powerful analytical method. Since its introduction in the early 1990s thin-layer chromatography(TLC)/matrix-assisted mass spectrometry (MALDI) has been used for analysis of a wide range of analytes including natural and synthetic organic compounds. Nowadays new desorption/ionization approaches have been developed and applied in conjunction with planar chromatography competing with MALDI. This review covers recent developments in the combination of TLC with various desorption/ionization MS methods which were made recent several years.